On the Optical Properties of Thin‐Film Vanadium Dioxide from the Visible to the Far Infrared. Issue 10 (20th August 2019) - Wan, Chenghao; Zhang, Zhen; Woolf, David; Hessel, Colin M.; Rensberg, Jura; Hensley, Joel M.; Xiao, Yuzhe; Shahsafi, Alireza; Salman, Jad; Richter, Steffen; Sun, Yifei; Qazilbash, M. Mumtaz; et al.
Abstract: The insulator‐to‐metal transition (IMT) in vanadium dioxide (VO2 ) can enable a variety of optics applications, including switching and modulation, optical limiting, and tuning of optical resonators. Despite the widespread interest in VO2 for optics, the wavelength‐dependent optical properties across its IMT are scattered throughout the literature, are sometimes contradictory, and are not available at all in some wavelength regions. Here, the complex refractive index of VO2 thin films across the IMT is characterized for free‐space wavelengths from 300 nm to 30 µm, using broadband spectroscopic ellipsometry, reflection spectroscopy, and the application of effective‐medium theory. VO2 films of different thicknesses are studied, on two different substrates (silicon and sapphire), and grown using different synthesis methods (sputtering and sol–gel). While there are differences in the optical properties of VO2 synthesized under different conditions, these differences are surprisingly small in the ≈2–11 µm range where the insulating phase of VO2 also has relatively low optical loss. It is anticipated that the refractive‐index datasets from this article will be broadly useful for modeling and design of VO2 ‐based optical and optoelectronic components, especially in the mid‐wave and long‐wave infrared. Abstract : The optical properties of vanadium dioxide (VO2 ) for wavelengths from 0.3 to 30 µm are described, as VO2 traverses its insulator‐to‐metal phase transition. A combination of characterization techniques and effective‐medium theory is used to explore films of different thicknesses, on different substrates, and grown using different methods, making the work broadly useful for modeling VO2 ‐based optical and optoelectronic components.